The Urgency of Establishing a Personal Data Protection Agency in Indonesia (Adopting the South Korean Personal Data Protection Agency Model) - Lubna Tabriz Sulthanah; Rasji Rasji (Universitas Islam Sultan Agung, 2025)
Countries under the constitution have a responsibility to protect the privacy of every citizen, one of which is through the protection of personal data. Indonesia has not yet had its own institution tasked with realizing the implementation of the protection of personal data in an integrated manner. Indonesia, when compared to several countries in the Southeast Asia and Asia region, can be said to be lagging behind in terms of having the PDP Law, including the absence of a Personal Data Protection Institution. As a policy study material to see the form of the Personal Data Protection Agency, the researcher will examine the Personal Information Protection Commission (PIPC), which is a personal data protection institution in South Korea. The selection of the country is based on the fact that South Korea is one of the countries in Asia that is considered to meet the equality standards of data protection laws. The type of research used is a normative legal research method supported by empirical legal research methods. The data collection technique was carried out by literature study supported by interviews with parties involved in the research. The main problem that will be raised in this study is how the Personal Data Protection Institutions in Indonesia and South Korea are similar and different. In addition, what is the urgency of establishing a Personal Data Protection Agency in Indonesia that adopts PIPC in South Korea. The adoption in question does not mean plagiarizing in a complete way, but adaptation by considering constitutional conditions, capacity, and specific needs.